Direct Neuronal Glucose Uptake Is Required for Contextual Fear Acquisition in the Dorsal Hippocampus - Kong, Liang; Zhao, Yan; Zhou, Wen-Juan; Yu, Hui; Teng, Shuai-Wen; Guo, Qi; Chen, Zheyu; Wang, Yue (Frontiers in Molecular Neuroscience, 2017)
The metabolism of glucose is a nearly exclusive source of energy for maintaining neuronal survival, synaptic transmission, and information processing in the brain. Two glucose metabolism pathways have been reported, direct neuronal glucose uptake and the astrocyte-neuron lactate shuttle (ANLS), which can be involved in these functions simultaneously or separately. Although ANLS in the dorsal hippocampus (DH) has been proved to be required for memory consolidation, the specific metabolic pathway involved during memory acquisition remains unclear. The DH and amygdala are two key brain regions for acquisition of contextual fear conditioning (CFC). In 2-NBDG experiments, we observed that 2-NBDG-positive neurons were significantly increased during the acquisition of CFC in the DH. However, in the amygdala and cerebellum, 2-NBDG-positive neurons were not changed during CFC training. Strikingly, microinjection of a glucose transporter (GLUT) inhibitor into the DH decreased freezing values during CFC training and 1 h later, while injection of a monocarboxylate transporter (MCT) inhibitor into the amygdala also reduced freezing values. Therefore, we demonstrated that direct neuronal glucose uptake was the primary means of energy supply in the DH, while ANLS might supply energy in the amygdala during acquisition. Furthermore, knockdown of GLUT3 by a lentivirus in the DH impaired the acquisition of CFC. Taken together, the results indicated that there were two different glucose metabolism pathways in the DH and amygdala during acquisition of contextual fear memory and that direct neuronal glucose uptake in the DH may be regulated by GLUT3.